Copper chloride complexes with substituted 4′-phenyl-terpyridine ligands: synthesis, characterization, antiproliferative activities and DNA interactions. Issue 23 (25th May 2021) - Li, Jiahe; Yan, Hao; Wang, Zhiyuan; Liu, Rongping; Luo, Baomei; Yang, Dengfeng; Chen, Hailan; Pan, Lixia; Ma, Zhen
Abstract : Eleven copper chloride complexes with substituted 4′-phenyl-terpyridine ligands: high antiproliferative activities against five human carcinoma cell lines, strong affinity for binding with DNA as intercalators and multiple molecular docking results. Abstract : Eleven copper chloride coordination compounds (1–11 ) with 4′-(4′-substituted-phenyl)-2, 2′:6′, 2′′-terpyridine ligands bearing hydrogen (L 1 ), cyano (L 2 ), p -hydroxyl (L 3 ), m -hydroxyl (L 4 ), o -hydroxyl (L 5 ), methoxyl (L 6 ), iodo (L 7 ), bromo (L 8 ), chloro (L 9 ), fluoro (L 10 ) or methylsulfonyl (L 11 ) were prepared and characterized by IR spectroscopy, elemental analysis and single crystal X-ray diffraction. Antiproliferative activities against tumor cells were investigated and DNA interactions were studied by circular dichroism spectroscopy and molecular modeling methods. In vitro data demonstrate that all the compounds exhibit higher antiproliferative activities as compared to cisplatin against five human carcinoma cell lines: A549, Bel-7402, Eca-109, HeLa and MCF-7. Compound 6 with methoxyl shows the best anti-proliferation activity. Spectrophotometric results reveal the strong affinity of the compounds for binding with DNA as intercalators and induce DNA conformational transitions. The results of molecular docking studies show that the compounds interact with DNA through π–π stacking, van der Waals forces, hydrophobic interactions and hydrogen bonds. The binding energies between compound 11 and three macromolecules, including DNA duplex, oligonucleotide and DNA–Topo I complex, are the lowest. The binding stability of compounds containing hydroxyl, methoxy and methylsulfonyl groups with biological macromolecules mainly relies on the hydrogen bonds. The ability of a compound to form hydrogen bonds can promote its binding to biological targets, thereby exhibiting high antiproliferative activity.